Patterns of species impoverishment in managed forests of Catalonia (NE Spain) (Journal of Vegetation Science, 2009)
Question: In managed forests, woody plant richness shows great variations in pattern. Herein we try to elucidate the role of major factors, such as successional status, to explain this variation. Assuming that less competitive or disturbance-sensitive species will be systematically more prone to disappear, we investigate the existence of nonrandom patterns of species impoverishment – i.e., the number of species unable to attain maximal richness – and the ecological and successional status of species associated with impoverishment in relation to a regional climatic gradient. Methods: We explored species composition in approximately 7500 forest plots in Catalonia (NE Spain). We evaluated non-random patterns of species impoverishment by analyzing their nestedness. Multivariate analysis was used to relate environmental variables and impoverishment to species occurrence. Plot successional status and ecological range were also estimated from species composition, and species impoverishment was then correlated to these estimators. Results: Most forests show a non-random pattern of species loss: poor stands tend to retain the same species, and the species determining high richness tend to be the same. Late successional species tend to be more common in impoverished plots of drier and warmer forests, while species typical of open or disturbed habitats are more common in impoverished plots of moister and colder forests. Communities dominated by early or late successional species are mostly impoverished, while the richest stands are constituted by species of intermediate stages. Forests dominated by species with a narrow or wide ecological range showed high impoverishment levels, while the richest stands had species with an intermediate ecological range. Discussion: In warmer Mediterranean forests, impoverishment tends to be associated with late successional stages, while in moister and colder forests, species loss is more closely related to disturbance and exploitation. This study reveals the difﬁculties involved in using species richness as a simple descriptor of the degree of forest conservation. Identiﬁcation of dominant species and species indicative of ecological processes would constitute an easily applicable practice that would consolidate assessment of forests status.